A Review of Rechargeable Zinc–Air Batteries: Recent Progress and Future Perspectives - Nazir, Ghazanfar; Rehman, Adeela; Lee, Jong‑Hoon; Kim, Choong‑Hee; Gautam, Jagadis; Heo, Kwang; Hussain, Sajjad; Ikram, Muhammad; AlObaid, Abeer A.; Lee, Seul‑Yi; Park, Soo‑Jin (Nano-Micro Letters, 2024)
Zinc–air batteries (ZABs) are gaining attention as an ideal option for various applications requiring high-capacity batteries, such as portable electronics, electric vehicles, and renewable energy storage. ZABs offer advantages such as low environmental impact, enhanced safety compared to Li-ion batteries, and cost-effectiveness due to the abundance of zinc. However, early research faced challenges due to parasitic reactions at the zinc anode and slow oxygen redox kinetics. Recent advancements in restructuring the anode, utilizing alternative electrolytes, and developing bifunctional oxygen catalysts have significantly improved ZABs. Scientists have achieved battery reversibility over thousands of cycles, introduced new electrolytes, and achieved energy efficiency records surpassing 70%. Despite these achievements, there are challenges related to lower power density, shorter lifespan, and air electrode corrosion leading to performance degradation. This review paper discusses different battery configurations, and reaction mechanisms for electrically and mechanically rechargeable ZABs, and proposes remedies to enhance overall battery performance. The paper also explores recent advancements, applications, and the future prospects of electrically/mechanically rechargeable ZABs. Highlights: 1 Recent progress in Zn–air batteries is critically reviewed. 2 Current challenges of rechargeable Zn–air batteries are highlighted. 3 Strategies for the advancement of the anode, electrolyte, and oxygen catalyst are discussed. 4 Future research directions are provided to design commercial Zn–air batteries.